Konzessionsabgaben und Länderfinanzausgleich: Probleme und Lösungsansätze der Einbeziehung der kommunalen Konzessionsabgaben in den Länderfinanzausgleich am Beispiel der Stadtstaaten - Michael Broer (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
Local authorities charge supply companies with concession dues on gas, water and electricity (Konzessionsabgaben), which are similar to some local taxes (local business tax, real property tax). These taxes have already been included in the fiscal equalization system and in the future concession dues should be treated alike. Its importance in revenue terms is an additional reason for this: concession dues amount to 1.8 bl. compared to real property tax of typ A of 0.3 bl. If concession dues are treated as mentioned above, payments in the fiscal equalization system may be strategically manipulated. First concession dues and their effects of the payments in the fiscal equalization system will be described. Then I will have a look at the aforementioned strategic policy and its effects on the payments and the arrangements to contain this strategic policy, which is exemplified by the so called city-states (Stadtstaaten).
Keywords: H29; H71; H77; 330; Horizontaler Finanzausgleich; Kommunale Einnahmen; Konzession; Gemeindesteuer; Deutschland